Valuation model of new start-up companies: Lithuanian case - Stankevičienė, Jelena; Žinytė, Santautė (Business: Theory and Practice, 2011)
A large number of economic, financial, social, technological, ecological, environmental and other indicators define the effectiveness of the investment process. According to some of the indicators, the alternative new venture companies are suitable for putting them into investment, according to others, they are not. It becomes difficult to choose the optimal investment in the new venture, as all of them have very poor accounting data or still do not have any. Therefore, there is a lack of valuation methods, which could evaluate start-ups without having any accounting data. The purpose of this article is to propose an evaluation model which could help to choose the optimal new venture to fund. Multi-criteria methods, used in the evaluation process, enable to get objective answers about the effectiveness of the optimal new venture comprehensively by presenting some generalized indicators and considering both quantitative and qualitative data. The start-ups evaluating method proposed by the authors has both theoretical and practical advantages: the extensive analysis can be carried out; the different classification of the evaluation criteria is possible; the weights of the criteria are evaluated (importance, significance), and the possibility to include the new evaluation criteria and their employment in practice are considered. The obtained empirical results comparing two Lithuanian start-ups show that the proposed method could be used for evaluating complex processes of the optimal new venture investments, and could be adapted for various situations.